Vegetation and soil natural defense: an experiment with students of basic education (Research, Society and Development, 2020)
This article describes actions performed in the Development Plan of the municipal school Domingos Gonçalves Gomes, in the city of Campo Grande-MS. The aim was to analyze the importance of vegetation on rainfall interception from a sample of Inga Fagifolia (a tree popularly known as ingazeiro), searching an approximation between scientific research and students of basic education. For this, a rainfall monitoring was performed by means of digital rain gauge and handmade analogue rain gauges – made by the students themselves. Monitoring the rates of rainfall interception by vegetation allowed new discussions in the classroom based on the fundamental concepts of Geography, especially Landscape. This research took place during the autumn of 2017 and was elaborated by the students of the 9th grade of Elementary School. The findings pointed out to the effectiveness of the use of handmade rain gauges, manufactured with PET bottles (two liters), during the rainfall monitoring and indicated that the Ingazeiro specimen can retain up to 86.67% of rainfall. The students realized the importance of vegetation for the soil protection and the importance of scientific research for generation data that will help with planning and environmental management. Finally, we expect that this project will be maintained, motivating more students to study through practical environmental education activities.